2023
DOI: 10.1039/d2tb02361j
|View full text |Cite
|
Sign up to set email alerts
|

ZIF-8 integrated with polydopamine coating as a novel nano-platform for skin-specific drug delivery

Abstract: Metal-organic frameworks (MOFs) are highly promising as a novel kind of drug delivery carrier; however, there are few reports about their application in nanoparticle-based formulations for dermal administration. In this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 73 publications
(116 reference statements)
0
8
0
Order By: Relevance
“…Considering the positive ζ potential of PCN-224, its electrostatic interaction with the negatively charged skin surface could potentially disrupt the integrity of the stratum corneum, as demonstrated in our previous study. 26 Such electrostatic interactions might facilitate the traversal of these nanoparticles across the dense barrier of the stratum corneum, and thus, the particle size would become a determining factor influencing penetration depth.…”
Section: Penetration Behaviors Of the Three-sized Pcn-224 In The Skinmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the positive ζ potential of PCN-224, its electrostatic interaction with the negatively charged skin surface could potentially disrupt the integrity of the stratum corneum, as demonstrated in our previous study. 26 Such electrostatic interactions might facilitate the traversal of these nanoparticles across the dense barrier of the stratum corneum, and thus, the particle size would become a determining factor influencing penetration depth.…”
Section: Penetration Behaviors Of the Three-sized Pcn-224 In The Skinmentioning
confidence: 99%
“…22−25 In the previous study, we demonstrated the feasibility of MOFs for improved dermal drug delivery by using zeolite imidazole framework-8 (ZIF-8) as a carrier of 5fluorouracil. 26 However, the research on the utilization of PCN-224 as a dermal or transdermal drug delivery carrier has been rarely realized and reported. Considering the possible insufficiency of the sole sensitizer, 27 it would be quite interesting to incorporate other kinds of sensitizers in PCN-224 for possible combined sonodynamic efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12) Recently, Wang et al coated ZIF-8 with dopamine to improve the skin targeting of 5-fluorouracil and facilitate drug delivery to deeper sites with the help of the hair follicle pathway. 141 In addition, other emerging inorganic NPs, such as metalorganic frameworks (MOF), and quantum dots (QDs), are flourishing. MOFs are mainly crystals composed of organic chains and metal ions.…”
Section: Inorganic-based Npsmentioning
confidence: 99%
“…12) Recently, Wang et al coated ZIF-8 with dopamine to improve the skin targeting of 5-fluorouracil and facilitate drug delivery to deeper sites with the help of the hair follicle pathway. 141…”
Section: Classifications Of Nps For Intracellular Cargo Deliverymentioning
confidence: 99%